Synthesized Nano-Titanium Dioxide (Nano-TiO2) via Ammonium Fluorotitanate ((NH4)2TiF6) Precipitation with Ammonia Solution - Yufeng Guo; Cong Zhou; Shuai Wang; Feng Chen; Yanqin Xie; Jinlai Zhang; Lingzhi Yang (Nanomaterials)
This study focuses on the chemical synthesis of nano-titanium dioxide (nano-TiO2) via ammonium fluorotitanate ((NH4)2TiF6) precipitation with ammonia solution, aiming to elucidate the effects of experimental parameters—including reaction temperature, duration, molar ratio of (NH4)2TiF6 to ammonia, and (NH4)2TiF6 concentration—on the particle size of synthesized nanoparticles, as well as the correlation between particle size and photocatalytic performance. The synthesized nanoparticles predominantly exhibited spindle-shaped morphology. Direct TEM imaging revealed the crystallization and growth mechanisms during synthesis: higher molar ratios, combined with lower temperatures and shorter durations, facilitated the formation of ultrafine particles, whereas lower molar ratios, with elevated temperatures and prolonged reaction times, yielded larger particles. Notably, nanorod structures emerged under low-temperature conditions with F− ion adsorption. To investigate the relationship between particle size and photocatalytic performance, a Taguchi method-inspired experimental design was employed to evaluate the positive or negative impacts of particle size on photocatalytic activity. An experimental matrix was constructed using coded values for each factor, and regression coefficients were calculated to quantify input-output correlations. Results demonstrate that titanium dioxide catalysts with a particle size range of 50–75 nm exhibit optimal photocatalytic efficiency.